Behavior and design of axially loaded web-stiffened stud walls. (December 2021) - Zhang, Zhuangnan; Wang, Chungang; Cheng, Daye; Hao, Guanwang; Yu, Lan
Abstract: The axial compression performance and design method of web-stiffened stud walls (with and without perforations) may be clearly distinguished from that of un-stiffened stud walls. The objective of this paper is to investigate the axial behavior of web-stiffened stud walls, and to provide a design method for these walls. A total of 10 cold-formed thin-walled steel stud walls—including different cross-sections, sheathing material, and web holes, were tested by being subjected to axial compression. The performance of different cross-sections, sheathing types, and perforated and non-perforated stud wall samples are discussed. A simplified finite element model of the walls is established and verified against the experimental results. Further, various parameter analyses are carried out to study the influence of the height, width, and spacing of the web holes. Finally, on the basis of the ultimate strength data obtained from the experimental and numerical results, an extension is proposed to the existing Direct Strength Method (DSM)—which uses elastic buckling loads provided by sheathing bracing—to enhance the ultimate strength of the un-stiffened stud walls. The results of this study explicitly show that the current use of the DSM overestimates the strengths of web-stiffened stud walls because local-distortional interactive buckling is not taken into account. Hence, two proposed methods, both of which consider the interaction of local and distortional buckling, are used to calculate the nominal axial strength of web-stiffened stud walls. A comparison of the calculation results with the numerical results demonstrates that the proposed method that is based on AS/NZS 4600:2018 is relatively accurate.